2016
DOI: 10.4049/jimmunol.1500383
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IFN-β Expression in the Spleen Is Restricted to a Subpopulation of Plasmacytoid Dendritic Cells Exhibiting a Specific Immune Modulatory Transcriptome Signature

Abstract: Type I IFNs are critical in initiating protective antiviral immune responses, and plasmacytoid dendritic cells (pDCs) represent a major source of these cytokines. We show that only few pDCs are capable of producing IFN-β after virus infection or CpG stimulation. Using IFNβ/YFP reporter mice, we identify these IFN-β–producing cells in the spleen as a CCR9+CD9− pDC subset that is localized exclusively within the T/B cell zones. IFN-β–producing pDCs exhibit a distinct transcriptome profile, with higher expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…Along this line, Bauer et al recently showed that upon treatment of IFN-␤ mob/mob mice with CpG, a stimulus for pDC but not mDC or PEC to produce type I IFNs (Fig. 1B), only a minor and distinct population of pDC within the spleen was stimulated to express the YFP reporter gene (48).…”
Section: Discussionmentioning
confidence: 81%
“…Along this line, Bauer et al recently showed that upon treatment of IFN-␤ mob/mob mice with CpG, a stimulus for pDC but not mDC or PEC to produce type I IFNs (Fig. 1B), only a minor and distinct population of pDC within the spleen was stimulated to express the YFP reporter gene (48).…”
Section: Discussionmentioning
confidence: 81%
“…In contrast to cDCs, pDCs exhibit an endosomal localization of TLR7 and TLR9 and a constitutive high expression of IRF7, which enables them to respond rapidly to viruses, bacteria or self‐nucleic acids . Specifically, due to their unique high expression of IRF7, pDCs are capable of producing large amounts of type I interferon and proinflammatory cytokines, immediately in response to stimulation . Furthermore, cytokines secreted by activated pDCs attract T cells and put them in close contact with DCs .…”
Section: Dendritic Cell Subset Functional Specializationsmentioning
confidence: 99%
“…Specifically, due to their unique high expression of IRF7, pDCs are capable of producing large amounts of type I interferon and proinflammatory cytokines, immediately in response to stimulation . Furthermore, cytokines secreted by activated pDCs attract T cells and put them in close contact with DCs . Brewitz et al .…”
Section: Dendritic Cell Subset Functional Specializationsmentioning
confidence: 99%
See 2 more Smart Citations